Raspberry PI based advanced communication for disaster management - Su. Suganthi, Dr; Aishwarya, S; Keerthana, S; R. Sandhya, B (International Journal of Engineering and Technology, 2018)
When a natural disaster occurs one of the major crisis is communication. This is mainly because when a calamity occurs all the cellular networks, towers and other contemporary means of network goes down making it impossible to communicate with others. Thus in this paper we propose an alternative solution for communication during disaster which can be achieved using a Long range radio transceiver module, which can operate without the help of any towers or base stations. The proposed transceiver model is a standalone device which can transmit and receive voice signals which operates on ISM band of frequency range 902 to 928 MHz, providing a hinderance free good communication, and as an additional feature is made to receive FM station signals using FM radio module, to keep us updated with the news, rescue and relief activities.Â